Preferences, prisoners and private information: was socrates rational at his trial? - GUHA, Brishti (Institutional Knowledge at Singapore Management University, 2011)
Using concepts from game theory, political economy, law and economics and the economics of asymmetric information, we describe the economics of one of the most famous trials in history—that of the Athenian philosopher Socrates. We discuss the question of whether Socrates’ actions during his trial were rational, using two different models. Our analysis sheds some light on institutional efficiency in trials that followed the classical Athenian pattern.